2013
DOI: 10.1136/emermed-2012-201942
|View full text |Cite
|
Sign up to set email alerts
|

Web-based general public opinion study of automated versus manual external chest compression

Abstract: The better 'advantages over disadvantages' score for the automated ECC device over manual ECC indicated that the general public might envisage use of the device. This could contribute to increase the frequency of resuscitation attempts by bystanders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nineteen studies, reported in 21 papers, met the criteria and were included for analysis. 7,2746 Characteristics of included studies are listed in Table 1. Four studies were rated on the quality of their methods as ‘good’ (their findings had a low risk of bias); eight were rated as ‘fair’; and seven were rated as ‘poor’ (their findings had a high risk of bias) (See S2 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen studies, reported in 21 papers, met the criteria and were included for analysis. 7,2746 Characteristics of included studies are listed in Table 1. Four studies were rated on the quality of their methods as ‘good’ (their findings had a low risk of bias); eight were rated as ‘fair’; and seven were rated as ‘poor’ (their findings had a high risk of bias) (See S2 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 13 studies were cross-sectional general population surveys and were eligible because the sample was segmented by a socio economic indicator with findings reporting potential barriers or facilitators for the lowest category of the socio-demographic indicator. Eight studies reported findings by education level, 28,30,33,34,4446 six by employment status or social class, 27,28,31,32,33,40 four by household income, 30,40,45,46 and one by neighbourhood income. 35 (Some studies reported by more than one indicator.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations